Determining the Levels of Zinc, Iron, Vitamin D, Renin Hormone, and Cystatin in Patients With Kidney Failure - Abdalrahim H. Eefan (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Kidney failure is characterized by impaired filtration function requiring dialysis and associated with metabolic and biochemical disturbances. Specific Background: This study evaluated zinc, iron, vitamin D, renin hormone, and cystatin C levels among 100 kidney failure patients treated at a dialysis center in Mosul between March and May 2025. Knowledge Gap: Conventional indicators of renal dysfunction lack sufficient sensitivity, necessitating integrated biochemical profiling to better characterize disease status. Aims: To determine variations in selected trace elements, hormones, and proteins and their association with demographic and clinical factors in kidney failure patients. Results: The findings revealed decreased zinc, iron, vitamin D, and renin levels alongside elevated cystatin C concentrations, particularly in the 50–60 age group. Iron deficiency was linked to dialysis-related blood loss, while zinc deficiency was associated with malnutrition or independent occurrence. Vitamin D deficiency was associated with fluid imbalance and renal dysfunction, though not directly linked to renin deficiency. Higher disease prevalence was observed among smokers, rural residents, individuals with low education levels, and those consuming unsafe water sources. Novelty: The study integrates multiple biochemical markers with demographic variables, highlighting cystatin C as a sensitive indicator of glomerular insufficiency compared with traditional measures. Implications: These results support routine monitoring of trace elements, vitamin D, renin activity, and cystatin C to improve early detection and guide clinical and public health strategies in kidney failure management. Highlights:• Reduced Trace Elements and Hormone Levels Accompanied by Elevated Cystatin Protein• Higher Disease Occurrence Linked to Age Group 50–60 and Lifestyle Factors• Cystatin Biomarker Identifies Glomerular Dysfunction More Sensitively Than Conventional Measures Keywords: Kidney Failure, Zinc, Iron, Vitamin D, Cystatin C